1983
DOI: 10.1139/g83-021
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal meiosis in alfalfa, Medicago sativa: cytology of 2N egg and 4N pollen formation

Abstract: The cytological mechanism of 2n egg formation was studied in several diploid (2n = 2x = 16) and tetraploid (2n = 4x = 32) clones of cultivated alfalfa (Medicago sativa L.). The comparison of normal megasporogenesis with megasporogenesis that produced 2n eggs was made using an ovule clearing technique with methyl salicylate. Developmental sequences in the formation of n and 2n eggs were the same through anaphase II. Following anaphase II in 2n egg formation cytokinesis occurred only in the micropylar diad, not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 3 publications
4
42
0
1
Order By: Relevance
“…It is well known that unreduced gametes or meiotic restitution is of predominant importance in polyploidization and speciation. This phenomenon has been reported in alfalfa (Pfeiffer and Bingham, 1983), barley (Finch and Bennet, 1979), potato (Conicella et al, 1996), and other species in Triticeae (Tiwari et al, 2008;Zhang et al, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…It is well known that unreduced gametes or meiotic restitution is of predominant importance in polyploidization and speciation. This phenomenon has been reported in alfalfa (Pfeiffer and Bingham, 1983), barley (Finch and Bennet, 1979), potato (Conicella et al, 1996), and other species in Triticeae (Tiwari et al, 2008;Zhang et al, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…Lack of meiotic cytokinesis is also considered as one of the reasons for unreduced gamete formation (PFEIFFER and BINGHAM, 1983;RAY and TOKACH, 1992). In potatoes, analysis of microtubule cytoskeletons has revealed that meiotic nuclear restitution occurs by the fusion of nonsister nuclei, which depends on the absence of secondary interzonal microtubules and on the distance between nuclei (CONICELLA et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 2n pollen was 40-fold more frequent than 4n pollen. Production of 4n pollen is documented in alfalfa, corn and peas, and generally involves a failure of cytokinesis following meiosis (Pfeiffer and Bingham, 1983). Additional cytological study is needed to understand the mechanisms underlying 2n and 4n pollen production in Achillea.…”
Section: Production Of Unreduced Pollen In Natural Populationsmentioning
confidence: 99%